Ubiquitous WLAN/camera positioning using inverse intensity chromaticity space-based feature detection and matching: A preliminary result - Wan Mohd Yaakob, Wan Bejuri; Mohd Murtadha, Mohamad; Maimunah, Sapri; Mohd Adly, Rosly (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.